Psychogenic Nonepileptic Seizures (PNES) in the Setting of Trauma and Schizophrenia - Chohan, Sikander; Chohan, Ali; Asif, Muhamid (Case Reports in Psychiatry, 2023)
Psychogenic nonepileptic seizures (PNES) are nonepileptic events characterized by seizure-like manifestations without abnormal electrical activity in the brain. Our case report illustrates the diagnostic journey of a young female with a history of schizophrenia and childhood trauma who had an initial misdiagnosis of epilepsy. The etiology of PNES is complex. Major depressive disorder and generalized anxiety disorder are common comorbid conditions in these patients. Additionally, previous trauma has been linked as a predisposing factor for the development of PNES. Psychotic disorders, specifically schizophrenia, have only recently been associated with PNES. We explore this relationship in depth, while also underscoring the diagnostic and treatment challenges of PNES that clinicians must remain aware of.